The association of prenatal and postnatal macrolide exposure with subsequent development of infantile hypertrophic pyloric stenosis: a systematic review and meta-analysis - Hamdi H. Almaramhy; Abdulmohsen H. Al-Zalabani (BMC, 2019)
Abstract Background The association between macrolides use and subsequent occurrence of infantile hypertrophic pyloric stenosis (IHPS) is still debatable. The aim of this study was to conduct a systematic review and meta-analysis of the association between perinatal exposure to macrolides, mainly erythromycin, and the development of pyloric stenosis. Methods Original studies were identified using MEDLINE, Web of Science, Scopus, Google Scholar, and the Cochrane Library databases. Studies investigating the association between perinatal exposure to macrolides and pyloric stenosis were included. The most adjusted effect estimates were pooled using random-effects meta-analysis. The I2 and Egger's tests were used to assess heterogeneity and publication bias, respectively. Results Fourteen papers (12 retrospective cohort studies and two case-control studies) were included. For postnatal exposure, the overall estimate of seven cohort studies indicated a statistically significant association (RR = 3.17, 95% CI: 2.38-4.23; I2 = 10.0%) with no evidence of publication bias (Egger P = 0.81). For prenatal exposure, six cohort studies and two case-control studies were included. Meta-analysis demonstrated a statistically significant association in the cohort studies (OR = 1.47, 95% CI: 1.03-2.09; I2 = 29.3%), but not in the case-control studies (OR = 1.02, 95% CI: 0.66-1.58; I2 = 51.2%). The overall pooled result was not statistically significant. Only two studies were included for exposure through breastfeeding, and the estimates did not show a statistically significant association (OR = 1.31; 95% CI: 0.42-4.1; I2 = 69.1%). Conclusions The study demonstrated good evidence of association between development of IHPS and direct postnatal exposure to macrolides. However, the evidence on the effects of prenatal exposure or postnatal maternal exposure (breastfeeding) is not conclusive.